Pinocchio - Zaki, Zaki Saied; ESC Creative Department ([Cairo] Educational Services Company, 2024)
Meet Pinocchio, a playful wooden puppet who wants more than anything, to be a real boy. With his cheerful spirit and curious heart, he sets off on a journey full of exciting adventures. Along the way, he learns the power of honesty, bravery, and kidness. Watch as Pinocchio's nose grows with every lie he tells, and cheer for him as he discovers that by being true to himself and others, dreams really can come true!
English Stories
Keywords: English stories